Pluronic F-127 Coated Zinc Oxide Nanoparticles Cytotoxicity And Their Photodynamic Therapy Towards Human Rt4 Urinary Bladder Cancer Cell Lines - Soud Abuelsamen, Abdulsalam Ali (2019)
Bladder cancer is the most common malignancy of the urinary system and one of the ten most common cancers that can affect the whole-body. Photodynamic therapy (PDT) holds promising applications in cancer treatment with high selectivity and minimum side effects. However, the current clinically approved photosensitizers have several drawbacks with limited tumour selectivity that affects the healthy normal cells. Zinc oxide nanoparticles (ZnO NPs) have exhibited promising potential in various biomedical applications including cancer therapy. In this study, for the first time, the potential of bare and Pluronic coated ZnO NPs as photosensitizers for effective photodynamic therapy against bladder cancer RT4 cell line were systematically investigated. The FESEM and TEM results revealed that Pluronic F-127 coated ZnO NPs had an average size of 80 nm whereby the Pluronic F-127 coating layer thickness ranged from 3 nm to 7 nm.